Mechanical Properties of Powder Metallugry (Ti-6Al-4V) with Hot Isostatic Pressing - Elfghi, M. A.; Gunay, M. (Engineering, Technology & Applied Science Research, 2020)
Titanium alloys are widely used due to their high performance and low density in comparison with iron-based alloys. Their applications extend to aerospace and military in order to utilize their high resistance for corrosion. Understanding the mechanical properties and microstructure of titanium alloys is critical for performance optimization, as well as their implications on strength, plasticity, and fatigue. Ti-6Al-4V is an α+β two-phase alloy and is considered one of the most commonly used titanium alloys for weight reduction and high-performance. To avoid manufacturing defects, such as porosity and composition segregation, Hot Isostatic Pressing (HIP) is used to consolidate alloy powder. The HIP method is also used to facilitate the manufacturing of complex structures that cannot be made with forging and casting. In the current research, Ti-6Al-4V alloys were manufactured with HIP and the impact on heat treatment under different temperatures and sintering durations on the performance and microstructure of the alloy was studied. The results show changes in mechanical properties and microstructure with the increase of temperature and duration.